Flavonoids’ and Other Polyphenols’ Pharmacological Activities for Phytopharmaceutical and Medicinal Applications (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
In today’s era of modern phytopharmaceutical and medicinal product development, the interest of industrial sectors and consumers in natural plant products, consisting of the bioactive molecules of flavonoids and other polyphenols, has remarkably increased. Furthermore, a significant number of extracts from medicinal plants and several traditional medicines have been researched to discover their major bioactive molecules. This provides powerful potential pharmacological activities to develop phytopharmaceutical and medicinal products, including seed compounds for pharmaceuticals, as well as cosmeceuticals, cosmetics, nutricosmetics, supplements, and other plant-based products with healthy benefits. This reprint is a part of Special Issue “Flavonoids’ and Other Polyphenols’ Pharmacological Activities for Phytopharmaceutical and Medicinal Applications”, which aims to explore the potential of natural plant products, especially the bioactive molecules of flavonoids and other polyphenols from interesting medicinal plants worldwide, as well as from several traditional medicines whose attractive efficacy for phytopharmaceutical and medicinal applications awaits discovery.